Dry land sustainable agriculture with application of sorgaab to improve brix sugar content and crop yield in two sorghum varieties. Issue 1 (April 2021) - Kusumastuti, A K; Harsono, P; Purwanto, E
Abstract: Sorgaab is an extract of Sorghum bicolor plant which can be used as a natural bioherbicide. This research aims to evaluate the effects of sorgaab application on brix sugar content and crop yield of two Sorghum varieties. Sorghum is a potential crop to be developed in Indonesia because it is beneficial for food, feed, energy, and sources of fiber. Sorghum can also live on marginal or dry land so that can adapt well to extreme agro-climate conditions. The research was conducted on dry land at Tambakan, Nguter, Sukoharjo, Indonesia with Vertisol soil type, using a Randomized Complete Block in Split Plot Design with 2 treatment factors: (1) Sorgaab concentration (S0 = control, S1 = 25%, S2 = 50%, S3 = 75%; and (2) Sorghum varieties (V1 = Numbu varieties, and V2 = Kawali varieties). Analysis of variance using F test 5%, continued with The Duncan Multiple Range Test. The relationships between variables using a correlation test. The application 75% of sorgaab showed the highest level of brix sugar content in Numbu varieties which is 16, 73% brix per plant and showed the highest level of 1000 grain weight in Kawali varieties which is 31, 889 grams. There is positive correlation between variables which the increase of sorgaab application followed by the increase of brix sugar content and crop yield of both two Sorghum varieties.